A version management system for SNOMED CT. - Ingenerf, Josef; Beisiegel, Thomas (Studies in health technology and informatics, 2008)
The parallel use of different versions of classifications and terminologies complicates the comparability of coded patient data. Annual adaptations of classifications like ICD-10 can be dealt with by using simple conversion tables. Terminologies like SNOMED CT have a much more complicate structure and biannual versions in different languages are offered in at least four representation formats. A version management system, called Terminology Version (TV) Manager, has been developed for searching and navigating in synchronized presentations of selected versions of SNOMED CT. Several functions for qualitative and quantitative comparisons of subtrees of interest are extended by accessing external software systems.
Keywords: Abstracting and Indexing as Topic; Database Management Systems; Information Storage and Retrieval; International Classification of Diseases; Medical Informatics Computing; Medical Subject Headings; Systematized Nomenclature of Medicine; Terminology as Topic; User-Computer Interface; Vocabulary, Controlled